Negation and naturalisation : tracing the logic of discovery in the Promotion of National Unity and Reconciliation Act 34 of 1995 - Modiri, Joel Malesela (University of Pretoria, 2025)
Thesis (PhD (Jurisprudence))--University of Pretoria, 2024.